PENGARUH KOMBINASI AKUPRESUR TITIK SANYINJIAO (SP6) DAN REBUSAN KAYU MANIS TERHADAP RED BLOOD CELL (RBC) PADA REMAJA DISMENORE - Cicin, Renildis; Desta Ayu Cahya Rosyida; Anik Latifah; Tetty Rihardini (Rena Cipta Mandiri, 2025)
Dysmenorrhea is menstrual pain that can interfere with adolescents’ daily activities and has the potential to decrease Red Blood Cell (RBC) levels, thereby increasing the risk of anemia. Anemia may affect learning concentration, productivity, and future reproductive health. Non-pharmacological therapies such as Sanyinjiao (SP6) acupressure and cinnamon decoction (Cinnamomum burmannii) are known to have the potential to increase RBC levels through improved blood circulation and natural antioxidant activity. This study aims to determine the effect of the combination of SP6 acupressure and cinnamon decoction on RBC levels among adolescents experiencing dysmenorrhea. The study employed a quantitative pre-experimental one-group pretest–posttest design. The study population consisted of 52 adolescents at the Youth Posyandu of Karang Asem Village, Klampis, Bangkalan, with a sample of 32 individuals selected through purposive sampling. The intervention was carried out for 5 days in the form of SP6 acupressure and consumption of cinnamon decoction twice daily. RBC levels were measured before and after the intervention using an automated hematology analyzer. The Paired t-test results showed a significant increase in RBC levels (p = 0.000). It is concluded that the combination of SP6 acupressure and cinnamon decoction is effective in increasing RBC levels among adolescents with dysmenorrhea.